Virus life cycle and the parthenogenesis of malignant catarrhal fever - Kumati, Osama B. Mohamed (2016)
Malignant catarrhal fever (MCF) is caused by two closely associated gamma herpes viruses namely alcelaphine herpesvirus 1 (AlHV-1) and ovine herpesvirus 2 (OvHV-2) and characterised with lymphocyte infiltration in non-lymphoid tissues, vasculitis and epithelial damage. The mechanism by which the viruses cause the disease is not fully understood. The hypothesis of this project was that MCF is initiated by aberrant gene expression in endothelium, epithelium and infected T cells of susceptible animals, because they are not the natural hosts for the viruses and the viruses will not have evolved in them. The first goal was to examine whether rabbit epithelium and bovine endothelium can be infected in vitro and in vivo with AlHV-1 using q PCR and, if infected whether viral transcripts could be identified in these tissue cells using q PCR and in situ hybridisation (ISH). The results revealed that endothelium and epithelium can be infected and latent infection can be established in them. This suggests the likelihood of establishing a similar type of infection in vivo. Secondly, the trial to identify latency-associated transcripts using 5-azacitidine treatment on bovine turbinate fibroblast (BT) cells and rabbit large granular lymphocytes (LGLs) was only partially successful. However, pan T antigen was expressed in 5-azacitidine treated but not untreated LGLs cells. This may indicate a function of the drug either directly or through the latency state. Transcriptome analysis in the infected and treated LGLs and BT cells showed that several pathways were affected by 5-aza although a possible latency (low transcript levels) was only seen in the BTs. Transcriptome analysis revealed similar pathways to those described for MCF in the tissues in vivo, and an effect of 5-aza on these. Viral transcripts analysis showed that genes related to productive/lytic cycles were higher than latent ones on day 17 of the in vivo experiment demonstrating that the virus may replicate at this stage of the disease. The attempt to localize the viral transcripts on the rabbit infected tissues using ISH was unsuccessful due to a lack of time.